Analisis Pengelolaan Kas pada PT. Grandhill Sengkang Kabupaten Wajo - Suharjum (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The aim of this research is to analyze the role of the cash budget and to analyze the effectiveness of using cash budget preparation at PT. Grandhill Sengkang, Wajo Regency. The analytical method used is a quantitative analysis method, the type of data used is primary data obtained directly from PT. Grandhill Sengkang, Wajo Regency. The results of the research that has been carried out show that 1) Implementation of the budget carried out by the company PT. Grandhill Sengkang, Wajo Regency has been able to act as a cash control tool. This is because the budget for cash receipts and expenditures is in accordance with the realization of cash receipts and expenditures, so it is easy for company managers to meet budget feasibility; 2) Preparation of the cash budget carried out by PT. Grandhill Sengkang Wajo Regency Tbk has been effective.